2023
DOI: 10.1108/jiabr-01-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

Zakat institutions’ adoption of social media

Abstract: Purpose This paper aims to explore the factors of social media adoption by zakat institutions. Design/methodology/approach This study uses qualitative data as the main source of evidence. Data were collected using semi-structured face-to-face interviews. Ten respondents from eight zakat institutions across Malaysia were interviewed. Judgement sampling and snowballing techniques were used to select respondents. Data analysis was done in three phases, namely, data reduction, data display and conclusion confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
1
12
0
1
Order By: Relevance
“…Findings -The research results show that (1) The Bengkulu Makmur program has a positive and significant effect on social care, meaning that as the Makmur program increases, mustahiq care more, (2) The Bengkulu Makmur program has a positive and significant effect on the welfare of mustahiq, (the more the Makmur program, the more prosperous the mustahiq will be), (3) Mustahiq's welfare has a positive and significant effect on mustahiq's social care, (the more prosperous the mustahiq is, the greater his concern for the environment), and (4) Welfare of mustahiq mediates the influence of the Bengkulu Makmur Program and social care in a positive and significant way (the more Makmur programs increase, the mustahiq's welfare and care for the environment also increase. Province.…”
Section: Purpose -mentioning
confidence: 90%
See 1 more Smart Citation
“…Findings -The research results show that (1) The Bengkulu Makmur program has a positive and significant effect on social care, meaning that as the Makmur program increases, mustahiq care more, (2) The Bengkulu Makmur program has a positive and significant effect on the welfare of mustahiq, (the more the Makmur program, the more prosperous the mustahiq will be), (3) Mustahiq's welfare has a positive and significant effect on mustahiq's social care, (the more prosperous the mustahiq is, the greater his concern for the environment), and (4) Welfare of mustahiq mediates the influence of the Bengkulu Makmur Program and social care in a positive and significant way (the more Makmur programs increase, the mustahiq's welfare and care for the environment also increase. Province.…”
Section: Purpose -mentioning
confidence: 90%
“…The Zakat system ensures proper distribution of wealth and has a far-reaching impact on the entire fabric of society. If zakat is established as an institution, it will create a collective social security scheme for mutual help/sympathy and its resources can be further utilized for social development (Abdullah & Suhaib, 2011). The results of the study (Shaikh, 2015) revealed that the collection of Zakat in Pakistan can reach 7% of total GDP and is considered sufficient to cover the poverty gap in Pakistan.…”
Section: Purpose -mentioning
confidence: 99%
“…In the times followed by technological advances, zakat organizations globally have gradually adopted the concept of technology in carrying out their operational activities (Salleh et al, 2017). Digital technology is also increasingly being used by zakat institutions in Indonesia, starting with the collection, distribution, and management of zakat and education related to zakat literacy (Abdullah et al, 2023;.…”
Section: Zakat Institutions and Online Platformsmentioning
confidence: 99%
“…One of them is that online zakat payment platforms are not widely utilized by the public, especially when compared to the number of individuals who still make zakat payments in the traditional offline manner. The factors influencing the acceptance and usage of these platforms need to be further understood to maximize their benefits in improving zakat distribution and community welfare (Abdullah et al, 2023;Syahputra & Mukhtasar, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…From a scholarly perspective, the purpose of zakat is said to encourage the development of pious, moral persons in that ‘ zakat moulds the individual into responsible caring persons. It inculcates the spirit of good will, cooperation, and brotherhood in upholding social solidarity in the society’ (Abdullah and Suhaib, 2011: 85).…”
Section: Muslim Charity and The Potential For Social Cohesion: Zakat ...mentioning
confidence: 99%